Closed versus open reviewing of journal manuscripts: how far do comments differ in language use? - Bornmann, Lutz; Wolf, Markus; Daniel, Hans-Dieter (Scientometrics, 2012)
Whereas in traditional, closed peer review (CPR) a few, selected scientists (peers) are included in the process of manuscript review, public peer review (PPR) includes, in addition to invited reviewers, a wider circle of scientists who are interested in a manuscript and wish to write a comment on it. In this study, using the data of two comprehensive evaluation studies on the CPR process at Angewandte Chemie—International Edition and the PPR process at Atmospheric Chemistry and Physics, we examined the language characteristics in comments that were written by invited reviewers in CPR and by invited reviewers and interested members of the scientific community in PPR. We used Linguistic Inquiry and Word Count (LIWC), a text analysis software program that counts words in meaningful categories (e.g., positive or negative emotions) using a standardized dictionary. We examined 599 comments from the reviews of 229 manuscripts. The results show that the comments in PPR are much longer than the comments in CPR. This is an indication that PPR reviewing has more of an improvement function and CPR reviewing has more of a selection function. The results also show that CPR is not, as might be expected, more susceptible to the expression of negative emotions than PPR is. On the contrary, positive emotion words are used statistically significantly more frequently in CPR than in PPR.